Complete Müllerian agenesis, renal agenesis, and renal ectopia: MURCS association – A rare cause of primary amenorrhea - Reddy Ravikanth; Pooja Majumdar (Apollo Medicine)
Müllerian duct aplasia–renal agenesis–cervicothoracic somite dysplasia (MURCS) association is a rare and unusual constellation of nonrandom findings that include Müllerian duct aplasia, renal aplasia, and cervicothoracic somite dysplasia. The agenesis of the Müllerian duct is the second-most common cause of primary amenorrhea after Turner syndrome. The abnormal development of Müllerian duct often associates with the urinary tract and skeletal abnormalities. MURCS association is a unique and rare developmental disorder with four common features of uterine hypoplasia or aplasia, renal agenesis or ectopy, vertebral anomalies, and short stature. Here, we report a 32-year-old female with aplasia of the Müllerian duct, unilateral renal agenesis, and anomalies of the cervicothoracic somites (MURCS association).